Can Work Engagement and Job Satisfaction Predict Employee Innovation? Case of Indian Telecom Employees - Jnaneswar, K. (Prabandhan: Indian Journal of Management, 2019)
Work engagement is a positive, fulfilling, work-related state of mind that is characterized by vigor, dedication, and absorption. This concept is gaining popularity because of the desirable outcomes it offers to both employers and employees. Job satisfaction describes the extent to which a person is satisfied in his/her present job. Its impact on organizational performance is well known. Employee innovation occurs when creative ideas are originated and implemented in the organization. Innovation is the need of the hour, and despite this, studies about innovation and its antecedents are sparse in the Indian context. The present study attempted to find out the impact of work engagement and job satisfaction on employee innovation. Data were collected from 165 employees working in various telecom organizations in Kerala by using convenient sampling technique. Job satisfaction was assessed using the Minnesota Satisfaction Questionnaire, Utrecht Work Engagement Scale (UWES) was used to measure work engagement, and employee innovation was measured by using the validated Corporate Innovation Survey questionnaire. The results revealed a significant positive relationship between work engagement, job satisfaction, and employee performance. It was also found that work engagement and job satisfaction individually as well as collectively impacted employee innovation. The study established that significant influence on employee innovation was more when work engagement and job satisfaction were combined. The study offered valuable insights to both practitioners and academicians by significantly contributing to the existing body of knowledge.